PENGEMBANGAN MEDIA INTERAKTIF BERBASIS GAMIFIKASI MENGGUNAKAN BAAMBOOZLE PADA MATA PELAJARAN IPAS KELAS IV SEKOLAH DASAR - Miftahul Riski; Nofri Hendri; Abna Hidayati, Alkadri Masnur (STKIP Subang, 2025)
This study aims to develop an interactive learning medium based on gamification using the Baamboozle platform for Grade IV elementary school students in the subject of Natural and Social Sciences (IPAS), particularly on the topic The Influence of Force Around Us. The research was motivated by the continued use of conventional teaching methods that make students less active, easily bored, and struggle to understand abstract concepts. The study employed a Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), involving Grade IV students of SDN 01 Muaro Pingai as the research subjects. Data collection instruments included material and media expert validation, teacher and student response questionnaires, as well as pre-test and post-test assessments. The findings showed that the Baamboozle-based interactive medium was rated “highly valid” in terms of both content and design, and received “very positive” responses from teachers and students who found it easy to use, engaging, and helpful in understanding the material. Effectiveness testing through N-Gain analysis resulted in an average score of 71.67% categorized as “fairly effective,” with students’ comprehension improvement classified as “high.” Thus, the interactive gamified medium using Baamboozle proved to be valid, practical, and effective as an alternative learning tool for IPAS, and it is expected to serve as a reference for teachers in creating more enjoyable, interactive learning experiences that enhance students’ motivation and learning outcomes.